The Development of Gating Drill Tool of Woodball Sports Branch on Central Java Woodball Athlete - Wicaksono, Wisnu; Rahayu, Tandiyo; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This research is conducted based on the athletes’ problems during gating drill. Therefore, the researcher is interested in researching the development of the drill tool to improve the basic swing technique in woodball sports. The objectives of this study are to: (1) produce a drill tool for gating technique for Central Java Woodball athletes. (2) Know the effectiveness of the toll for basic gating techniques training skills for Central Java woodball athletes. This research was development research that was conducted in Central Java; the purpose was to produce gating drill tool products. The subject of this study involved 7 Central Java athletes. Through development research steps to produce products, the final product was obtained in the form of gating drill development model. The indicators of the success of this product are in the form of analysis of observations, questionnaires, discussions with woodball experts, woodball trainers, Central Java woodball athletes, and the documentation of all test subjects in the research. The conclusions of this study are (1) Gating drill products are feasible and can be used as a means of gating drill for Central Java Woodball athletes. (2) The gating drill product is effectively used as a tool to improve the basic swing technique of woodball on Central Java Woodball athletes. The results of the analysis related to the effectiveness of the use of gating drill tools reached a good category. Hence, it is concluded that the tool was suitable for use as a gating drill tool.